Cyclin-dependent kinase inhibitors AZD5438 and R547 show potential for enhancing efficacy of daunorubicin-based anticancer therapy: Interaction with carbonyl-reducing enzymes and ABC transporters - Sorf, Ales; Novotna, Eva; Hofman, Jakub; Morell, Anselm; Staud, Frantisek; Wsol, Vladimir; Ceckova, Martina (Biochemical pharmacology, 2019)
Daunorubicin (DAUN) has served as an anticancer drug in chemotherapy regimens for decades and is still irreplaceable in treatment of acute leukemias. The therapeutic outcome of DAUN-based therapy is compromised by its cardiotoxicity and emergence of drug resistance. This phenomenon is often caused by pharmacokinetic mechanisms such as efflux of DAUN from cancer cells through ATP-binding cassette (ABC) transporters and its conversion to less cytostatic but more cardiotoxic daunorubicinol (DAUN-OL) by carbonyl reducing enzymes (CREs). Here we aimed to investigate, whether two cyclin-dependent kinase inhibitors, AZD5438 and R547, can interact with these pharmacokinetic mechanisms and reverse DAUN resistance. Using accumulation assays, we revealed AZD5438 as potent inhibitor of ABCC1 showing also weaker inhibitory effect to ABCB1 and ABCG2. Combination index analysis, however, shown that inhibition of ABCC1 does not significantly contribute to synergism between AZD5438 and DAUN in MDCKII-ABCC1 cells, suggesting predominant role of other mechanism. Using pure recombinant enzymes, we found both tested drugs to inhibit CREs with aldo-keto reductase 1C3 (AKR1C3). This interaction was further confirmed in transfected HCT-116 cells. Moreover, these cells were sensitized to DAUN by both compounds as Chou-Talalay combination index analysis showed synergism in AKR1C3 transfected HCT-116, but not in empty vector transfected control cell line. In conclusion, we propose AZD5438 and R547 as modulators of DAUN resistance that can prevent AKR1C3-mediated DAUN biotransformation to DAUN-OL. This interaction could be beneficially exploited to prevent failure of DAUN-based therapy as well as the undesirable cardiotoxic effect of DAUN-OL.
Keywords: psi; vazba proteinů; daunomycin; proliferace buněk; Protein Binding; Cell Line, Tumor; Humans; Imidazoles; Dogs; Antineoplastic Agents; lidé; imidazoly; ATP Binding Cassette Transporter, Subfamily G, Member 2; Cloning, Molecular; regulace genové exprese enzymů; proteiny spojené s mnohočetnou rezistencí k lékům; Multidrug Resistance-Associated Proteins; Neoplasm Proteins; Cell Proliferation; Gene Expression Regulation, Enzymologic; chemorezistence; Pyrimidines; nádorové proteiny; Animals; vazebná místa; zvířata; Heart Diseases; nádorové buněčné linie; Drug Resistance, Neoplasm; ABC transportér z rodiny G, člen 2; nemoci srdce; protinádorové látky; Binding Sites; klonování DNA; pyrimidiny; Daunorubicin